Interpreting ciliopathy-associated missense variants of uncertain significance (VUS) in Caenorhabditis elegans. Issue 10 (20th November 2021) - Lange, Karen I; Best, Sunayna; Tsiropoulou, Sofia; Berry, Ian; Johnson, Colin A; Blacque, Oliver E
Abstract: Better methods are required to interpret the pathogenicity of disease-associated variants of uncertain significance (VUS), which cannot be actioned clinically. In this study, we explore the use of an animal model ( Caenorhabditis elegans ) for in vivo interpretation of missense VUS alleles of TMEM67, a cilia gene associated with ciliopathies. CRISPR/Cas9 gene editing was used to generate homozygous knock-in C. elegans worm strains carrying TMEM67 patient variants engineered into the orthologous gene ( mks-3 ). Quantitative phenotypic assays of sensory cilia structure and function (neuronal dye filling, roaming and chemotaxis assays) measured how the variants impacted mks-3 gene function. Effects of the variants on mks-3 function were further investigated by looking at MKS-3::GFP localization and cilia ultrastructure. The quantitative assays in C. elegans accurately distinguished between known benign (Asp359Glu, Thr360Ala) and known pathogenic (Glu361Ter, Gln376Pro) variants. Analysis of eight missense VUS generated evidence that three are benign (Cys173Arg, Thr176Ile and Gly979Arg) and five are pathogenic (Cys170Tyr, His782Arg, Gly786Glu, His790Arg and Ser961Tyr). Results from worms were validated by a genetic complementation assay in a human TMEM67 knock-out hTERT-RPE1 cell line that tests a TMEM67 signalling function. We conclude that efficient genome editing and quantitative functional assays in C. elegans make it a tractable in vivo animal model for rapid, cost-effective interpretation of ciliopathy-associated missense VUS alleles.